The relationship between maternal age and the incidence of anemia in pregnancy - Arum Seftiani Lestari; Silvia Finida Hannisa; Yunida Haryanti; Rizki Amartani; Paskalia Tri Kurniati; Yolanda Montessori; Ervina Elny Frisillya Kuhuparuw (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Anemia in pregnancy remains an important maternal health problem and may contribute to maternal and fetal morbidity. Maternal age is one of the characteristics that may be associated with anemia, particularly when pregnancy occurs before 20 years or after 35 years of age. Purpose: To analyze the relationship between maternal age and the incidence of anemia during pregnancy. Method: This quantitative study used an observational analytical design with a cross-sectional approach. The study population comprised 137 pregnant women who underwent antenatal check-ups at Sungai Durian Community Health Center from October to December 2025. A total of 133 respondents met the study criteria and were selected using total sampling. Secondary data were obtained from medical records and included maternal age and hemoglobin status. Data were analyzed using the Pearson Chi-Square test at α = 0.05, and the odds ratio (OR) with a 95% confidence interval (CI) was reported. Results: Most respondents were in the non-risk maternal age group of 20–35 years (65.4%), while 34.6% were in the risk age group (<20 or >35 years). Anemia was identified in 49 respondents (36.8%). The Pearson Chi-Square test showed a significant association between maternal age and anemia in pregnancy (p = 0.008). Pregnant women in the risk age group had 2.705 times higher odds of anemia than those aged 20–35 years (OR = 2.705; 95% CI = 1.288–5.681). Conclusion: Maternal age was significantly associated with anemia in pregnancy. Pregnant women aged <20 or >35 years require closer screening and monitoring for anemia during antenatal care. Suggestion: Health workers should strengthen early anemia screening among pregnant women in the risk age groups and provide appropriate nutrition education and counseling on adherence to iron supplementation.